Mendukung Kepemimpinan Pendidikan yang Bijaksana: Kepemimpinan Imperatif dan Langkah-Langkah Memajukan Program Pembelajaran dalam Rangka Mempersiapkan Pendidikan Abad ke 21 sebagai Abad Pengetahuan dalam Perspektif Al Qur’an dalam Term Ijtihad - Padi, Achmad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Wise leadership (education) will direct its ranks to wise teaching as well, grow from honing the main vision of teaching, gathering and reflecting various relevant information about the development of the current situation and embodying clarity of vision, and building further steps from the development of the current situation , and hierarchically compiled a team to study and implement all developments by holding on to the main normative keys of the Qur'an and Hadith. The purpose of this study is to describe efforts to support wise educational leadership: imperative leadership and steps to advance learning programs in order to prepare for 21st century education as a century of knowledge in the perspective of the Qur'an. From the discussion it was concluded that: to advance education and learning programs in schools, the school ranks, especially the principal, as the motorbike do the following things: 1) guided by the main key to change, namely the Qur'an and Hadith; 2) linking school elements and stakeholders in adjusting various aspects of the system and educator practices that contribute to learning achievement; 3) explore data updates on externally locally, regionally and nationally in order to identify current problems and plan internal improvements; 4) planning the development of educational programs to improve student achievement (short and long term); 5) consider the benefits of building support for change in improving educational programs from teachers, administrators, students, parents, education boards, and the wider community